Development of the Halal Industry Towards the Growth of the Islamic Economy in Indonesia - Dhefara Harsaning Djati; Rosadi, Danang (ASEAN Journal of Halal Study, 2025)
As a country with the largest Muslim population in the world, Indonesia actually has great potential for the development of the halal and sharia industry. Unfortunately, this potential has not been matched by good achievements at the global level. The halalness of a product is a mandatory requirement for every consumer, especially Muslim consumers. Be it products in the form of food, medicine or other consumer goods. The halal product industry is currently experiencing development not only as a halal product but also as a halal lifestyle. This research is a normative legal research with the research method being library research. Based on the results of the study, it is known that with the birth of Law Number 33 of 2014 concerning Halal Product Guarantee, there is a guarantor and legal certainty regarding the guarantee of halal products. To become a major player in the world’s halal industry, full support from the government is needed. The halal industry roadmap needs to be made as soon as possible so that the goals and development of the halal industry in Indonesia are more focused. The existence of the National Sharia Finance Committee (KNKS) is also expected to help the development of the halal industry in Indonesia.